Carbamazepine induces hepatotoxicity in zebrafish by inhibition of the Wnt/β-catenin signaling pathway. (1st May 2021) - Bai, Zhonghui; Jia, Kun; Chen, Guilan; Liao, Xinjun; Cao, Zigang; Zhao, Yangqi; Zhang, Chunping; Lu, Huiqiang
Abstract: As drug abuse has become increasingly serious, carbamazepine (CBZ) is discharged into the aquatic environment with municipal sewage, causing potential harm to aquatic organisms. Here, we utilized zebrafish, an aquatic vertebrate model, to comprehensively evaluate the hepatotoxicity of CBZ. The larvae were exposed to 0.07, 0.13, and 0.26 mmol/L CBZ from 72 hpf to 144 hpf, and the adults were exposed to 0.025, 0.05, and 0.1 mmol/L CBZ for 28 days. The substantial changes were observed in the size and histopathology of livers, indicating that CBZ induced severe hepatoxicity in the larvae and adults. Oil red O staining demonstrated CBZ exposure caused severe lipid accumulation in the livers of both larvae and adults. Furthermore, CBZ exposure facilitated hepatocyte apoptosis through TUNEL staining, which was caused by rising ROS content. Subsequently, down-regulation of genes related to the Wnt pathway in exposure groups indicated that CBZ inhibited the development of liver via the Wnt/β-catenin signaling pathway. In conclusion, CBZ induced severe hepatotoxicity by promoting lipid accumulation, generating excessive ROS production, and inhibiting the Wnt/β-catenin signaling pathway in zebrafish. The results reveal the occurrence of CBZ-induced hepatotoxicity in zebrafish and clarify its mechanism of action, which potentially illustrate environmental concerns associated with CBZ exposure. Graphical abstract: Image 1 Highlights: Carbamazepine induced severe hepatotoxicity by promoting hepatocyte apoptosis. . Carbamazepine impaired the tissue morphology of the liver in zebrafish. Carbamazepine resulted in lipid accumulation and oxidative stress in zebrafish liver. Carbamazepine induced severe hepatotoxicity via inhibition of Wnt/β-catenin signaling pathway.